2000
DOI: 10.1073/pnas.97.16.9093
|View full text |Cite
|
Sign up to set email alerts
|

Gastrulation Defective is a serine protease involved in activating the receptor Toll to polarize the Drosophila embryo

Abstract: The dorsoventral axis of the Drosophila embryo is induced by a ventrally restricted ligand for the receptor Toll. The Toll ligand is generated by a proteolytic processing reaction, which occurs at the end of a proteolytic cascade and requires the gastrulation defective (gd), nudel, pipe, and windbeutel genes. Here we demonstrate that the GD protein is a serine protease and that the three other genes act to restrict GD activity to the ventral side of the embryo. Our data support a model in which the GD protease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…That depiction strongly resembled a Drosophila melanogaster protease called gastrulation defective (GD), which is a 72-kD extracellular Ser protease involved in a protease cascade leading to dorsal-ventral signaling (Konrad et al, 1998;Han et al, 2000;DeLotto, 2001;Dissing et al, 2001;LeMosy et al, 2001). After purification and partial sequencing, it became clear that GD and SAS-1 and SAS-2 are structurally unrelated, although they may share some similar biological characteristics.…”
Section: Heparin and Autoproteolysismentioning
confidence: 99%
“…That depiction strongly resembled a Drosophila melanogaster protease called gastrulation defective (GD), which is a 72-kD extracellular Ser protease involved in a protease cascade leading to dorsal-ventral signaling (Konrad et al, 1998;Han et al, 2000;DeLotto, 2001;Dissing et al, 2001;LeMosy et al, 2001). After purification and partial sequencing, it became clear that GD and SAS-1 and SAS-2 are structurally unrelated, although they may share some similar biological characteristics.…”
Section: Heparin and Autoproteolysismentioning
confidence: 99%
“…Because our previous studies had suggested that GD activity depends on proteolytic processing, we initially tested the activities of two truncated GD forms. GD⌬N1 lacks amino acids 1 through 211 after signal sequence cleavage, where Lys-211 is the nearest basic residue N-terminal to the conserved catalytic domain and thus might serve as a cleavage site for GD activation (6,13). GD⌬N2 lacks amino acids 1 through 253, corresponding to a potential cleavage site suggested by Konrad et al (13) at the beginning of the conserved catalytic-domain sequence.…”
Section: Gd Triggers a Proteolytic Cascade By Activating Snake That Imentioning
confidence: 99%
“…Our recent studies have suggested that GD, the next downstream protease from Nudel, plays a more clearly instructive role in triggering the Toll signaling pathway (6). Unusual structural features of GD have made it uncertain whether this protein functions as a protease (13).…”
mentioning
confidence: 99%
“…4D). Members of group 1 are predicted to have one helix between Cys 3 and Cys 4 and one helix centered on a cysteine of the linker. A detailed analysis of group 1 reveals four subgroups depending on the number of cysteines in the linker (1a-1d).…”
Section: -Loop Prevents Access To the Activation Site-mentioning
confidence: 99%